Physical Characteristics of Immobilized Cells Acetobacter xylinum of Various Concentrations of Na-alginate - Indraningtyas, Lathifa; Kustyawati, Maria Erna; Fitriah, Nafiatul (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2024)
Immobilization of Acetobacter xylinum cells by trapping technique is considered one way to maintain cell viability and can be used repeatedly. The purpose of this study was to determine the physical characteristics of immobilized cells in different concentrations of Na-alginate and apply them to the manufacture of nata de coco, as well as to see the surface and pore shape of immobilized cells after fermentation. This study used a descriptive method with visual observation. This study used one factor, namely various concentrations of Na-alginate, namely 2%, 3%, 4%, and 5% w/v. The immobilized cells applied to the manufacture of nata de coco had only a Na-alginate concentration of 3% resulting in a nata fiber layer close to that of a control. Immobilized cells with a Na-alginate concentration of 2% have a cracked, slightly pore surface with a size of 60.37 Î¼m, while a Na-alginate concentration of 5%, have a smooth surface, many pores, with a size of 10.55 Î¼m. Thus, the concentration affects the characteristics of immobilized cells. Application of immobilized cells with a Na-alginate concentration of 3% produces nata de coco with a fairly thick and stable fiber layer characteristic (close to control).